Nurse practitioner–mediated intervention for preoperative control of diabetes in elective surgery patients. Issue 10 (29th April 2016) - Garg, Rajesh; Metzger, Cheyenne; Rein, Raquel; Lortie, Meghan; Underwood, Patricia; Hurwitz, Shelley; Bader, Angela; Carbone, Kyle; Schuman, Brooke
Abstract: Purpose: This study evaluated the effect of nurse practitioner (NP) mediated interventions on diabetes control before elective surgery. Data sources: A program was initiated to improve preoperative diabetes control in patients with HbA1c > 8%. The intervention was initially mediated by a physician alone and subsequently changed to involve NPs. The goal of intervention was fasting blood glucose (BG) <200 mg/dL on the day of surgery (DOS). Data were collected before the program (control group), during physician‐mediated intervention (phase 1), and during NP‐mediated intervention (phase 2). Conclusions: There were 222 patients in the control group, 226 in phase 1, and 160 in phase 2. Mean BG (mg/dL) on DOS was 171.4 ± 66.5 in control group, 162.6 ± 58.1 in phase 1, and 153.4 ± 46.6 in phase 2 ( p = NS for control vs. phase 1 and <0.01 for control vs. phase 2). More patients received an intervention in phase 2 (93%) than in phase 1 (75%). Among those receiving intervention, 87% achieved target BG in phase 2 and 82% in phase 1 ( p = NS). Duration of diabetes, baseline HbA1c, time available before surgery, and diabetes intervention were independent predictors of achieving target BG. Implications for practice: NP‐mediated interventions increased access to care and resulted in lower BG levels and may be a good strategy for preoperative diabetes control.